Literatur Review Terhadap Penelitian Agresivitas Pajak - Sri Ayem; Umi Wahidah; Wirandi Wirandi; Fransiska Theodosia Peni Yan; Anisa Alfiana; Dini Fitrianingsih; Sisilia Marlita Arce Kaka; Karolina Tunga (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The purpose of this study was to examine and analyze the influence of apparatus competence, internal control systems, organizational commitment and community participation on village fund management accountability. This research method uses a Systematic Literature Review (SLR) or Library Research or library research approach. This reference source was obtained from 20 journals published through the Google Scholar database. The results of the study show that apparatus competence, internal control systems, organizational commitment and community participation have an effect on the accountability of managing village funds. The implications of the findings of this study are to encourage accountable village fund management through increasing the competency of village fund management officials, village government organizational commitment, and community participation. Keywords: Village Apparatus Competence, Organizational Commitment, Internal Control System, Community Participation.